2016
DOI: 10.1002/stem.2407
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: One Stone for Multiple Birds: Generating Universally Compatible Human Embryonic Stem Cells

Abstract: With ongoing clinical trials, human embryonic stem cells (hESCs) have shown substantial potential for regenerative medicine. However, due to the mismatch of human leukocyte antigens (HLAs) between hESC-derived allografts and recipients, immunosuppressant regimens must be used to prevent immune rejection of the grafts. Considerable efforts have been devoted to overcoming this hurdle via the derivation and banking of human nuclear transfer ESCs, parthenogenetic ESCs, and induced pluripotent stem cells. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Some of the current methods for CM purification still have concerns including inadvertent gene editing, possibly causing misreading and deletions that could further change the phenotype of derived‐CMs and increase the heterogeneity of the cell population. By using a precisely inserted locus like AAVS1, a stable cell line can be established after long‐term selection . Then, efficiency of CM differentiation and reproducibility can be increased.…”
Section: Remaining Challenges Of Using Pscs For MI Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the current methods for CM purification still have concerns including inadvertent gene editing, possibly causing misreading and deletions that could further change the phenotype of derived‐CMs and increase the heterogeneity of the cell population. By using a precisely inserted locus like AAVS1, a stable cell line can be established after long‐term selection . Then, efficiency of CM differentiation and reproducibility can be increased.…”
Section: Remaining Challenges Of Using Pscs For MI Therapymentioning
confidence: 99%
“…Though the study was performed on a small number of animals, their results demonstrate the promise of the MHC match system for use in preclinical trials. To overcome immune rejection after transplantation, gene editing has also emerged as a powerful tool to knock out immune receptors such as B2M, CIITA, and MHCII . It is also suggested that administration of MSCs along with PSC‐CMs may confer an immune suppressive effect due to the MSCs that can decrease the T and B cell activation.…”
Section: Remaining Challenges Of Using Pscs For MI Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, knockdown of both HLA class I and class II in hESC could provoke T-cell ignorance in vitro and protection from xenogeneic immune rejection in vivo (6062). Disruption of MHC class II transactivator in hESCs leads to the silencing of HLA class II expression in differentiated cells, such genetic modification could confer protection from the allogeneic helper T cells (63, 64). While the immune evasive properties of these cells lacking HLA I and II molecules have been confirmed in vitro and in mice, they remain to be evaluated in the context of a human immune system.…”
Section: Strategies To Protect Allogeneic Human Pluripotent Stem Cellmentioning
confidence: 99%